2020
DOI: 10.3390/ijerph17041221
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Prepregnancy Body Mass Index, Gestational Weight Gain, and Risk of Adverse Perinatal Outcomes in Taiwan: A Population-Based Birth Cohort Study

Abstract: Epidemiological studies have shown that maternal prepregnancy body mass index (BMI) and gestational weight gain (GWG) are associated with increased risk of perinatal outcomes. However, the evidence of such associations in Asian populations is limited. We conducted a secondary data analysis to investigate the relationships of prepregnancy BMI and GWG with the risks of adverse perinatal outcomes, including gestational diabetes (GDM), gestational hypertension (GHTN), preeclampsia, cesarean delivery, preterm birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
0
21

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 51 publications
9
41
0
21
Order By: Relevance
“…The inconsistency in previous literature might result from differences in study designs, study populations, sample sizes and various breastfeeding outcome definitions. In our previous study, the prevalence of underweight was greater in Taiwan than in the United States and European countries [11,24]. It is unclear whether pre-pregnancy underweight status may have a certain effect on breastfeeding behaviors from a population with a higher proportion of women who are underweight.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The inconsistency in previous literature might result from differences in study designs, study populations, sample sizes and various breastfeeding outcome definitions. In our previous study, the prevalence of underweight was greater in Taiwan than in the United States and European countries [11,24]. It is unclear whether pre-pregnancy underweight status may have a certain effect on breastfeeding behaviors from a population with a higher proportion of women who are underweight.…”
Section: Introductionmentioning
confidence: 88%
“…The survey contents include comprehensive information about prenatal care history, dietary behaviors, parental health status, family socioeconomic status, and the growth and development of the offspring. A detailed history of the TBCS has been previously provided elsewhere [1,24,25].…”
Section: Data Source and Study Populationmentioning
confidence: 99%
“…Women with obesity may be unaware of the extent of adverse health outcomes of pregnancy that are related to obesity and may hold misconceptions about the relationship between diet, weight, and health in pregnancy 40–42 . Advice should be given to women with obesity of the effect on their fertility and the risks of obesity during pregnancy and childbirth, which include neural tube defects, macrosomia, preterm delivery, stillbirth, shoulder dystocia, cesarean delivery, GDM, metabolic syndrome, sleep apnea, hypertension, and thromboembolic disorders 37,43–45 .…”
Section: Figo Guidance For Prepregnancy Obesitymentioning
confidence: 99%
“…While the amount of gestational weight gain considered “normal” will vary regionally, consider advising pregnant women with obesity and a singleton pregnancy to limit gestational weight gain to approximately 5–9 kg to reduce the risk of adverse pregnancy outcomes 43,45,64 . This is based on the Institute of Medicine guidelines (IOM) 65 .…”
Section: Figo Guidance For Pregnancy Obesitymentioning
confidence: 99%
“…However, the conclusions of various studies on the correlation between pre-pregnancy BMI and PTB appear to be paradoxical. It was reported that the risk of PTB in women with pre-pregnancy high BMI was significantly increased (Baeten et al 2001;Chen et al 2020;Cnattingius et al 1998;Cnattingius et al 2013;Weiss et al 2004;Zhou et al 2019), whereas other studies contradicted this result, suggesting that women with a high pre-pregnancy BMI could have a protective impact on PTB (Chen et al 2013;Khashan & Kenny 2009;Sebire et al 2001). Furthermore, similar results have also been reported on association between pre-pregnancy BMI and LBW (Li et al 2020;Ronnenberg et al 2003a;Wu et al 2020).…”
Section: Introductionmentioning
confidence: 68%